Block copolymer nanoparticles remove biofilms of drug-resistant gram-positive bacteria by nanoscale bacterial debridement - Li, Jianghua (2018)
Biofilms and the rapid evolution of multidrug resistance complicate the treatment of bacterial infections. Antibiofilm agents such as metallic–inorganic nanoparticles or peptides act by exerting antibacterial effects and, hence, do not combat biofilms of antibiotics-resistant strains. In this Letter, we show that the block copolymer DA95B5, dextran-block-poly((3-acrylamidopropyl) trimethylammonium chloride (AMPTMA)-co-butyl methacrylate (BMA)), effectively removes preformed biofilms of various clinically relevant multidrug-resistant Gram-positive bacteria including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococci (VRE V583), and Enteroccocus faecalis (OG1RF). DA95B5 self-assembles into core–shell nanoparticles with a nonfouling dextran shell and a cationic core. These nanoparticles diffuse into biofilms and attach to bacteria but do not kill them; instead, they promote the gradual dispersal of biofilm bacteria, probably because the solubility of the bacteria–nanoparticle complex is enhanced by the nanoparticle dextran shell. DA95B5, when applied as a solution to a hydrogel pad dressing, shows excellent in vivo MRSA biofilm removal efficacy of 3.6 log reduction in a murine excisional wound model, which is significantly superior to that for vancomycin. Furthermore, DA95B5 has very low in vitro hemolysis and negligible in vivo acute toxicity. This new strategy for biofilm removal (nanoscale bacterial debridement) is orthogonal to conventional rapidly developing resistance traits in bacteria so that it is as effective toward resistant strains as it is toward sensitive strains and may have widespread applications.